Flash‐Induced Ultrafast Production of Graphene/MnO with Extraordinary Supercapacitance. Issue 7 (18th June 2021) - Zhang, Huihui; Yang, Dan; Ma, Tianyi; Lin, Han; Jia, Baohua
Abstract: Production of high‐capacitance electrodes beyond the theoretical limit of 550 F g −1 of pure graphene materials is highly desired for energy storage applications, yet remains an open challenge, especially with a facile and simple process. By rational design of reaction condition guided by theoretical analysis, the ultrafast (within millisecond) fabrication of high‐performance graphene/MnO electrodes via a low‐cost and one‐step flash reduction process is proposed and demonstrated. This simple method enables high‐quality porous graphene networks and the effective synthesis of embedding pseudocapacitive‐active MnO nanomaterials simultaneously. Due to the high‐density and homogeneous distribution of MnO nano‐needles on 3D graphene networks, an ultrahigh capacitance (up to 1706 F g −1 based on electrode mass and 2150 F g −1 based on MnO mass only) is demonstrated. Functional supercapacitor prototype further illustrates the broad potential applications enabled by the fabricated electrodes in energy storage, sensing, and catalysts. Abstract : Ultrafast production (within several milliseconds) of graphene/MnO electrodes is demonstrated by a simple and green flash reduction process. Guided by the in‐depth understandings from theoretical analysis, MnO nano‐needles can be anchored homogenously onto 3D graphene networks. An extraordinary capacitance up to 1706 F g −1 is obtained by the fabricated electrodes, which can be assembled into a ready‐to‐use supercapacitor coin cell to power up electronic devices.